Strategi Dakwah Terhadap Pembinaan Perilaku Keagamaan Remaja Masjid Baitul Ikhsan Koto Majidin Hilir Kabupaten Kerinci Provinsi Jambi - Akbar, Rizal Nur; Ravico, Ravico; Mirdad, Jamal (Journal of Da'wah, 2023)
Adolescents are the young generation and part of the national assets as a hope for the future of the nation, state and religion. The behavior of teenagers at the Baitul Ikhsan mosque is still found to lack Islamic behavior such as lack of worship at the mosque and playing more games. Therefore, efforts are needed to improve the religious behavior of teenagers of the Baitul Ikhsan mosque, one of which is by implementing a da’wah strategy towards fostering the religious behavior of teenagers of the Baitul Ikhsan mosque, Koto Majidin Hilir Village, Kerinci Regency, Jambi Province. This type of research uses qualitative research. Data collection techniques using observation, interview and documentation methods. The subject of this research is the youth coach of the Baitul Ikhsan Mosque. Mosque teenagers. Baitul Ikhsan teenage parents and the community of Koto Majidin Hilir Village with a total of 45 people. The research results on the Da‟wah Strategy towards the Development of Religious Behavior of Adolescents of the Baitul Ikhsan Mosque Koto Majidin Hilir, Kerinci Regency, Jambi Province. The role of the Baitul Ikhsan Mosque youth in shaping the character of adolescents is quite good in carrying out activities and playing an active in these activities. The supporting factor for the Baitul Ikhsan Mosque youth is the source of funds that is useful for organizing all mosque youth activities. The inhibiting factor for the Baitul Ikhsan Mosque teenagers is the busyness of the spirit of the management which decreases so that it affects the development of religious behavior of the Baitul Ikhsan Mosque teenagers in Koto Majidin Hilir Village